Template for Diced Cartilage with Platelet-Rich Fibrin (PRF) in Rhinoplasty: An Easy Solution for Millimetric Camouflage of the Full Dorsal Esthetic Unit - Beaudoin, Pier-Luc; Carles, Guillaume (Facial Plastic Surgery, 2023)
Dorsal irregularities are one of the most common issues in modern rhinoplasty. Rhinoplasty surgeons propose placing interface grafts lining the hole dorsum to ensure a natural unoperated look. Diced cartilage embedded in Choukroun's platelet-rich fibrin (PRF) scaffold being one of the most recent innovations in the field. However, no method has been described to help with the creation of thin, malleable, and reproductive graft with millimetric precision using that technique. The senior author details his protocol and his experience with a newly developed template for the creation of reproductive grafts with standard size and thickness, using diced cartilage, injectable PRF (iPRF), and advanced PRF (aPRF), for full dorsal camouflage and lining in rhinoplasty. This retrospective case series was conducted to evaluate the results looking at the dorsal esthetic unit at a minimum of 6 months for patients who beneficiated from a millimetric dorsal augmentation from 1 to 2mm using diced cartilage with iPRF and aPRF. The author reports his experience with 54 cases operated from April 2018 to May 2022 using his newly developed template.The template is an innovative technique to allow faster and more reliable fabrication of soft grafts using diced cartilage with both iPRF and aPRF. This novel approach allows for millimetric dorsal augmentation from 1 to 2mm with great precision and high reproductivity with good esthetic outcome.
Keywords: rhinoplasty; dorsum; PRF; template; reconstruction